1996
DOI: 10.1172/jci118833
|View full text |Cite
|
Sign up to set email alerts
|

Diverse effects of Glut 4 ablation on glucose uptake and glycogen synthesis in red and white skeletal muscle.

Abstract: The ability of muscles from Glut 4-null mice to take up and metabolize glucose has been studied in the isolated white EDL and red soleus muscles. In EDL muscles from male or female Glut 4-null mice, basal deoxyglucose uptake was lower than in control muscles and was not stimulated by insulin. In parallel, glycogen synthesis and content were decreased. Soleus muscles from male Glut 4-null mice took up twice more deoxyglucose in the absence of insulin than control muscles, but did not respond to insulin. In fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
73
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 37 publications
10
73
2
Order By: Relevance
“…Similar findings in EDL muscle were made in generalized GLUT-4(Ϫ/Ϫ) mice (35). They are, however, at variance with recent observations showing that in EDL muscle of both female and male GLUT-4(Ϫ/Ϫ) mice glycogen content is decreased (30).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Similar findings in EDL muscle were made in generalized GLUT-4(Ϫ/Ϫ) mice (35). They are, however, at variance with recent observations showing that in EDL muscle of both female and male GLUT-4(Ϫ/Ϫ) mice glycogen content is decreased (30).…”
Section: Discussionsupporting
confidence: 82%
“…However, in female GLUT-4(Ϫ/Ϫ) mice the glycogen content in soleus muscle was significantly increased (30). Muscle-specific GLUT-4 knockout mice showed a normal resting glycogen level in both soleus and EDL muscle (22).…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore possible that GLUT12 can act as a substitute for GLUT4 in fetal tissues and allow increased uptake of glucose into cells in the presence of insulin or IGF-I. In adult GLUT4 global knockout mice, glucose homeostasis is essentially normal and glucose uptake is normal or increased in soleus muscle (Katz et al 1995;Stenbit et al 1996). It was suggested that expression of another glucose transporter protein compensated for the lack of GLUT4.…”
Section: Discussionmentioning
confidence: 99%
“…Overall the unexpected non-diabetic phenotype of GLUT4-null mice has suggested a compensatory mechanism or unmasking of a novel glucose transporter activity. Indeed in vitro analysis demonstrated a 2.3-fold increase in basal glucose uptake in GLUT4-null male and normal basal levels with a significant increase following insulin stimulation in GLUT4-null female oxidative soleus muscles [116]. The possibility that overexpression of GLUT1 and/or ectopic expression of other canonical GLUTs occurred in GLUT4-null soleus muscle was ruled out [32,116].…”
Section: Glut4mentioning
confidence: 99%
“…Indeed in vitro analysis demonstrated a 2.3-fold increase in basal glucose uptake in GLUT4-null male and normal basal levels with a significant increase following insulin stimulation in GLUT4-null female oxidative soleus muscles [116]. The possibility that overexpression of GLUT1 and/or ectopic expression of other canonical GLUTs occurred in GLUT4-null soleus muscle was ruled out [32,116]. As a result, expression of a novel GLUT4-independent glucose transport activity was proposed [32,108,116].…”
Section: Glut4mentioning
confidence: 99%